Optimalisasi Instagram Guna Meningkatkan Daya Saing UMKM Soto Ayam Cak Pon melalui Pendampingan Digital Marketing - Muhamad Amir Ariandi; Yunita Yunita; Amelia Yusnita; Muhammad Rinaldi; Nardi Nardi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This community service program aims to enhance the competitiveness of the MSME Soto Ayam Cak Pon by optimizing the use of Instagram as a digital marketing tool. The mentoring activities were carried out through a hands-on practice approach to ensure that the business owner could directly understand and apply various Instagram business features. Data collection techniques included observation, interviews, and documentation to identify the partner’s initial needs and to assess improvements in digital literacy after the mentoring process. The results indicate that the MSME owner successfully created a business email, developed and optimized an Instagram account, arranged an informative business profile, linked WhatsApp contact and business location, and produced reels content to support visual promotion. The activation of the professional dashboard also enabled the owner to monitor account performance and understand audience engagement patterns. These improvements demonstrate that structured social media utilization can expand promotional reach and strengthen the business’s market presence. This program highlights the essential role of digital literacy in improving the competitiveness of culinary MSMEs in the digital era and serves as a foundation for further development of sustainable digital marketing strategies.